2021
DOI: 10.3389/fpsyg.2021.668550
|View full text |Cite
|
Sign up to set email alerts
|

Manipulations of List Type in the DRM Paradigm: A Review of How Structural and Conceptual Similarity Affect False Memory

Abstract: The use of list-learning paradigms to explore false memory has revealed several critical findings about the contributions of similarity and relatedness in memory phenomena more broadly. Characterizing the nature of “similarity and relatedness” can inform researchers about factors contributing to memory distortions and about the underlying associative and semantic networks that support veridical memory. Similarity can be defined in terms of semantic properties (e.g., shared conceptual and taxonomic features), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 133 publications
(184 reference statements)
0
10
0
Order By: Relevance
“…Many experimental paradigms have been used to study human memory and its failings. One of the most popular is Deese-Roediger-McDermott (DRM) paradigm (for the review, see: REF 17 ), used for studying memory distortions, because of its simplicity, controllability, and flexibility 18 . In this paradigm, participants study a list of related words, each of which converges on a non-studied critical lure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many experimental paradigms have been used to study human memory and its failings. One of the most popular is Deese-Roediger-McDermott (DRM) paradigm (for the review, see: REF 17 ), used for studying memory distortions, because of its simplicity, controllability, and flexibility 18 . In this paradigm, participants study a list of related words, each of which converges on a non-studied critical lure.…”
Section: Introductionmentioning
confidence: 99%
“…This variant of the DRM task allows to effectively separate the encoding (presentation of the memory set) and retrieval processes (remembering whether or not the recognition probe was presented in the preceding memory set). While most DRM tasks focus on the distorting effects of semantic similarity, memory distortions due to phonological similarity (based on surface/structural content) are also investigated 17 , 18 . In a review by Chang and Brainerd (2021) 18 , the authors showed that there are differences between semantic and phonological distortions examined using DRM paradigm under both short-term and long-term memory conditions as well as due to the test modality (auditory versus visually presented items).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to increasing recall and recognition performance, survival processing may also be expected to prevent false memories (Otgaar & Smeets, 2010 ). False memories are defined as the memory trace of an experience that in fact did not happen or remembering it in a different way than the fact (Roediger & McDermott, 1995 ) and can arise due to various factors, including inferences that a person makes regarding the event (Roediger & McDermott, 1995 ), which can be influenced by interference of events that happened afterward (e.g., Loftus et al, 1978 , Schooler et al 1990 , Goff et al 1998 , Tversky et al 2000 ), sleep deprivation (Chatburn et al, 2017 ), and similarity between to be remembered information (Coane et al, 2021 ), or general metacognitive beliefs about how memory works (Mazzoni & Kirsch, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…On a subsequent memory test, critical lures are often mistakenly recalled or recognized (e.g., Arndt and Beato, 2017;Pitarque et al, 2018;Huff et al, 2020;Beato and Arndt, 2021). While this paradigm produces robust false memory, there is substantial variability in the false recognition that occurs across DRM lists (e.g., Gallo and Roediger, 2002;Beato and Díez, 2011;Cadavid and Beato, 2017;Coane et al, 2021).…”
Section: Introductionmentioning
confidence: 99%